Effect of Transformational Leadership Behaviour on Employees’ Career Development in Zenith International Bank (ZIB) Plc, North East 3 Zone, Adamawa State, Nigeria: Post COVID-19 Pandemic Experience (International Journal of Scientific Research and Management (IJSRM), 2024)
The World Health Organisation (WHO) declared the coronavirus (COVID-19) pandemic as a global pandemic. The pandemic has left organisations with a number of challenges, including decreased revenue, decreased consumer spending, poor marketing outcomes, firm closures, reduced staff motivation, virtual working, increasing unemployment, and changes in service delivery and lifestyle. However, due to the rapid growth in global competition, advancements in technology, innovativeness, and growing demands for better customer service, organisational leaders were challenged to devise performance-improvement strategies in order to survive the challenges posed by COVID-19, particularly in Deposit Money Banks (DMBs). Against this backdrop, this study investigates the impact of transformational leadership (TL) behaviours on employee career development (i.e. employee mentoring and coaching). This study conceptualised TL behaviours as idealized influence, inspirational motivation, intellectual stimulation, and individual consideration, while career development as career coaching and career mentoring. The study used an explanatory survey research approach with a sampl of 130 employees from four (4) branches of Zenith International Bank Plc North East 3 Zone, Adamawa State. This study’s data were collected via questionnaire. Descriptive statistics such as mean, standard deviation and correlation were used in analysing the data collected, while study’s hypotheses were tested using the multiple regression technique. The regression results show that TL behaviours such as inspirational motivation, intellectual stimulation, and individual consideration have favourable significant effect on career development (Mentoring and coaching). While idealised influence has significant adverse effects on career development in both career mentoring and coaching. Overall, the findings indicate that TL positively and strongly predicts career development (i.e. career mentoring and coaching). As a result, this study concludes that TL actions are critical for organisational development and should be supported by managers since they improve employees’ career progression within the organisation and have significant effects on numerous employee outcomes.